1972
DOI: 10.1002/1097-4679(197210)28:4<455::aid-jclp2270280405>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Stress-related social events and psychological impairment

Abstract: PROBLEMThis study investigated the relationship between stress-related social events and psychological impairment. Other researchers@) have suggested that there are both qualitative and quantitative relationships between stress-related social events and psychiatric impairment. Beisser and Glasser ( l ) found that marital and occupational stress accounted for more than two-thirds of admissions to mental hospitals. These findings parallel those of Gurin, et al., (2), who surveyed a general population and found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Life events, therefore, have been conceptualized as contributing to the stress that leads to psychopathology. However, most relationships between life events and pathology have been found in largely neurotic outpatient samples, while most studies with inpatients (Aponte & Miller, 1972;Lahniers & White, 1976;Ulenhuth & Paykel, 1973) have found small or no relationships.…”
mentioning
confidence: 99%
“…Life events, therefore, have been conceptualized as contributing to the stress that leads to psychopathology. However, most relationships between life events and pathology have been found in largely neurotic outpatient samples, while most studies with inpatients (Aponte & Miller, 1972;Lahniers & White, 1976;Ulenhuth & Paykel, 1973) have found small or no relationships.…”
mentioning
confidence: 99%
“…Aponte and Miller (1972) found no significant correlation between the number and severity of symptoms and scores from the SRE. Garrity, Marx, and Somes (1978) collected correlations between behavioral pathology and life events prior to and after the events occurred.…”
Section: Previous Researchmentioning
confidence: 91%
“…The above results tend to support a significant relationship between life stress and future illness; however, other investigators found negative results using retrospective designs. Aponte and Miller (1972) found no significant correlation between the number and severity of symptoms and scores from the SRE. Garrity, Marx, and Somes (1978) collected correlations between behavioral pathology and life events prior to and after the events occurred.…”
Section: Life Stress and Psychological And Physical Illnessmentioning
confidence: 91%